Workshop Pengelolaan Data Inventaris Pada GPDI Jemaat Bethesda Kampung Kwadeware Distrik Waibu - Wonar, Klara; Nababan, Dytha Meninta; Simanjuntak, Aaron MA; Herlina Bleskadit, Novalia; Karoma, Yulianti (The Community Engagement Journal, 2025)
This community service activity aims to enhance the capacity for inventory data management of assets at GPdI Bethesda Congregation, Kwadeware Village, Waibu District, Jayapura Regency. The method used was a participatory workshop comprising material presentation and hands-on asset data collection practice. The workshop was attended by 30 participants, including the pastor, vice pastor, and congregation members. The results demonstrated an increase in participants' understanding of the importance of church asset inventory based on ISAK 35 principles, as well as the systematic identification of all church assets through inventory cards. Participant evaluation showed a high level of satisfaction with an expectation for ongoing mentoring. It was concluded that this workshop successfully raised the awareness and capacity of the congregation in managing church assets transparently and accountably, while also providing an asset database for future planning and decision-making. Keywords: asset inventory, GPdI, ISAK 35, community service, church governance